2021
DOI: 10.3389/fevo.2020.617948
|View full text |Cite
|
Sign up to set email alerts
|

Applications of eDNA Metabarcoding for Vertebrate Diversity Studies in Northern Colombian Water Bodies

Abstract: Environmental DNA metabarcoding is a tool with increasing use worldwide. The uses of such technology have been validated several times for diversity census, invasive species detection, and endangered/cryptic/elusive species detection and monitoring. With the help of this technology, water samples collected (n = 37) from several main river basins and other water bodies of the northern part of Colombia, including the Magdalena, Sinú, Atrato, and San Jorge river basins, were filtered and analyzed and processed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…This threshold approach recovered a minimum number of reads ranging from 12 to 15 ( N = 4, sequencing libraries). Other studies that implemented similar read thresholds include Mojica and Caballero (2021), Broadhurst et al (2021) and Sales et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This threshold approach recovered a minimum number of reads ranging from 12 to 15 ( N = 4, sequencing libraries). Other studies that implemented similar read thresholds include Mojica and Caballero (2021), Broadhurst et al (2021) and Sales et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…This threshold approach recovered a minimum number of reads ranging from 12 to 15 (N = 4, sequencing libraries). Other studies that implemented similar read thresholds include Mojica and Caballero (2021) 3 (308,53,184) 7 (1111, 17, 41, 582, 52, 112, 143) 10 (42, 99, 95, 124, 133, 198, 482, 930, 25, 570) 1 ( 382)…”
Section: Sequence Analysis and Taxonomic Assignmentmentioning
confidence: 99%
“…From the 85 fish taxa detected, we were able to identify only 22 at the species level and 51 at the genus taxonomic level. This limitation was possibly due to incomplete reference data of local species in genomic databases, which has also been reported for other ecosystems within the Neotropics (Cilleros et al, 2019;Milan et al, 2020;de Santana et al, 2021;Jackman et al, 2021;Mariac et al, 2021;Sales et al, 2021;Lozano Mojica & Caballero, 2021;Batista et al, 2021;Cantera et al, 2022;Mariac et al, 2022;Coutant et al, 2023), especially for the 12S marker used in this study (Cilleros et al, 2019;de Santana et al, 2021;Jackman et al, 2021). We selected the 12S marker because it was previously reported to be used to assess fish diversity with success, not only in sea and deepwater environments (Miya et al, 2015;Riaz et al, 2011;Thomsen et al, 2016;Valentini et al, 2016), but also in freshwater from neotropical systems (Jackman et al, 2021;Milan et al, 2020;Sales et al, 2021;Teixeira et al, 2021) and the tropics in general (Blackman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al (2021b) utilized a combination of visual effort for individual observation and indirect evidence (feces and feeding records) based mainly on the skills of experienced former manatee hunters in identifying the presence of the animals, while Brice (2014) and Ruano et al (2021) used a fish finder side-scan sonar to detect Amazonian manatees' presence in the evaluated area. Additionally, Hunter et al (2018) suggested the use of eDNA as a tool for estimating the occurrence of Amazonian manatee, as promising results have been obtained with T. manatus in the wild (Lozano-Mojica & Caballero, 2021). Although these techniques have been shown to be useful to detect the presence of manatees, an efficient method to estimate density and abundance has not yet been developed; the low number of detections over a wide and variable area remains a challenge for the development of abundance and density estimates.…”
Section: Habitat Distribution and Populational Aspectsmentioning
confidence: 99%